ESTUDO RETROSPECTIVO DE 98 FELINOS SUBMETIDOS À ACUPUNTURA ATENDIDOS EM SERVIÇO DE REABILITAÇÃO E DOR CRÔNICA - Figueiredo, Nuno Emanuel Oliveira; Joaquim, Jean Guilherme Fernandes; Luna, Stelio Pacca Loureiro; Cápua, Maria Luísa Buffo De; Santos, Bianca Paiva Rodrigues Dos (Universidade Federal de Goiás, 2018)
Abstract This is a retrospective survey with the aim of investigate the clinical cases of cats attended at a rehabilitation and chronic pain control service during 13 years. The aim of this study was to analyze the efficacy and methods of acupuncture, evaluate clinical evolution and the patient profile in 98 clinical charts. The clinical outcome data showed that 69.7% of patients improved after treatment with acupuncture, 16.7% had no significant response and 13.6% died. No patient had worsening, despite three of nine animals that died were due to progression of the primary disease treated only with acupuncture. The main indications for the use of acupuncture in cats at the clinic were neurological diseases - particularly trauma in the spinal cord and brain - where there was an improvement in 53.7% of the animals. Treatment was considered successful in neurological cases, when animals regained independent locomotion and in cases of spinal disease, when neurological scores changed for IV or V to I or II. Dry needle acupuncture was the most used technique for the treatment, with 94.7% of prevalence, followed by electroacupuncture (30.6%) and laserpuncture (21.4%). The mean number of acupuncture sessions were 6.97±14.97. It was concluded that acupuncture was efficient to treat most of the cats with different clinical conditions, showing that these species probably respond as well as dogs after acupuncture treatment.

Resumo Este estudo retrospectivo avaliou os casos clínicos de felinos atendidos em Serviço de Reabilitação e Dor Crônica, durante 13 anos, totalizando 98 prontuários. Os objetivos deste estudo foram caracterizar o perfil do paciente atendido e avaliar a eficácia da acupuntura (AP) e dos métodos associados a esta técnica no tratamento de doenças em felinos e respectiva evolução clínica. Constatou-se que 69,7% dos pacientes melhoraram após tratamento com AP, 16,7% não apresentaram resposta significativa e 13,6% vieram a óbito. Não foram registrados casos de piora relacionados ao tratamento com AP, embora, dos nove animais que vieram a óbito, três foram devido à progressão da doença primária tratada exclusivamente com AP. As principais afecções tratadas foram relacionadas ao sistema nervoso - sobretudo trauma medular e encefálico - em que se registrou uma melhora em 53,7% dos animais. O tratamento foi considerado eficaz quando os pacientes recuperaram a capacidade normal de deambulação e em casos de doenças medulares quando o escore neurológico mudou de IV (grave) ou V (muito grave) para I (normal) ou II (leve alteração). A técnica de agulha seca foi a mais utilizada para os tratamentos, com 94,7% de prevalência, seguida da eletroacupuntura (30,6%) e da laserpuntura (21,4%). O número de sessões totais de AP foi em média de 6,97±14,97, sendo as mesmas semanais. Conclui-se que o estímulo de acupontos utilizando diferentes métodos foi eficiente para tratar a maioria dos gatos com diversas condições clínicas, evidenciando que esta espécie provavelmente responde tão bem como os cães após o tratamento de AP.
RETROSPECTIVE STUDY OF 98 CATS SUBMITTED TO ACUPUNCTURE ATTENDED AT A REHABILITATION AND CHRONIC PAIN CONTROL SERVICE
Keywords: chinese traditional medicine; cats; primary research; clinics; neurology; medicina tradicional chinesa; gatos; pesquisa primária; clínica; neurologia